Translating Islamic Values into Post-Flood Spiritual Parenting: A Phenomenologically Oriented Qualitative Study of Primary School Teacher-Parents in Aceh - Herawati, Herawati; Hayati, Cut Intan; Pardi, Pardi (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2026)
Purpose – This study analyzes the experiences of teacher-parents in translating Islamic values into spiritual parenting to support children’s sense of safety, meaning-making in the face of adversity, and restoration of routines after floods in Aceh. Design/methods/approach – This phenomenologically oriented qualitative study involved eight teacher-parents with primary school-aged children affected by floods in Aceh Tamiang, North Aceh, Pidie Jaya, and Pidie, as well as three contextual informants. Data were collected from January to March 2026 through semi-structured interviews, supported by a short questionnaire, field notes, and documentation. Data were analyzed through reflexive thematic analysis with a phenomenological orientation. Interpretive traceability was supported through source comparison, reflective memos, member checking with six participants, and an audit trail. Findings – From the perspective of teacher-parents, floods disrupted children’s sense of safety, family routines, and school activities. Five interrelated spiritual parenting practices emerged: ṣabr (patience) as a means of calming children and supporting emotion regulation; tawakal linking effort, preparedness, and prayer; qadha and qadar as a framework for making sense of adversity; the habituation of worship and prayer to restore order; and parental role modelling. Teaching experience helped participants use simple language, concrete examples, repetition, and age-appropriate adaptations. Originality/Value – This study proposes a conceptual model of post-flood spiritual parenting based on family pedagogy that encompasses emotion regulation, meaning-making of uncertainty, and restoration of routines. Practical Implications – The findings may serve as an initial reference for families and schools to integrate responsive communication, simple preparedness, learning and worship routines, and home-school coordination. Spiritual parenting is positioned as a family support resource, not as a substitute for psychosocial support or professional referral for children with prolonged distress.